Effect of educational intervention based on health belief model on psychological factors of AIDS preventive behaviors in addicts - Fateme Bastami; Naser Sharafkhani; Katayoun Bakhteyar; Mohmmad Heydari; Akbar Hassanzadeh; Firoozeh Mostafavi (Gonabad University of Medical Sciences, 2017)
AIDS is a problem threatening public health throughout the world, especially developing countries. Injecting drug users are most at risk of HIV infection and account for 68.15% of all suffering cases in Iran. This study investigated the effect of health intervention on the AIDS preventive behaviors among addicts based on HBM. This was a quasi-experimental research with pretest-posttest design. The study sample comprised 88 randomly selected male addicts being kept at rehabilitation centers in Khorramabad, Iran. The participants were randomly assigned to intervention and control groups. Data were collected through questionnaire designed to assess health belief model structures as well as knowledge, and behavior domains. The educational content was designed, edited, and executed after the analysis of pretest results. The intervention group received 3 sessions each of 90 minutes. Two months after the intervention, the posttest was performed using the same questionnaire. The results showed that mean scores of perceived benefits, self-efficacy, susceptibility, severity, knowledge, and preventive behaviors significantly increased in the intervention group after the intervention while the mean score of perceived barriers significantly decreased. Based on the results of this study, of this survey, it can be concluded that an increase in the score of health belief model structures including perceived susceptibility, perceived severity, and perceived benefits could result in adopting preventive behaviors against AIDS. Therefore, this survey confirms the efficacy of health belief model in adopting AIDS preventive practices among addicts.